Rapid laboratory tests for malaria detection in Japan - Kashihara, Naoko (J Gen Fam Med, 2017)
Although malaria is not a common disease in Japan, malaria can be a mortal illness. The malaria rapid diagnostic immune‐chromatographic test (ICT) enables a more rapid and easier diagnosis of malaria. [Image: see text]